102 POTENTIAL: developing a paediatric colorectal bowel function and life quality tool led by human-computer design expertise. (23rd February 2023) - Briggs, Lydia; Lindert, Judith; Jiang, Cedric; Bryant, William A; Key, Daniel; Shah, Mohsin; Bowyer, Stuart A; Spiridou, Anastassia; Sivaraj, Jayaram; Blackburn, Simon; Curry, Joe; Sebire, Neil J; et al.
Abstract : The quality of life of a patient post-surgical intervention is important for the long-term monitoring and treatment of patient disease. In addition to a patient's journey in terms of what procedures, ward admissions, laboratory tests and radiology appointments they undergo during their time in hospital, quality of life assessments in the form of questionnaires are vital in the monitoring of patient health once they have been discharged. All these different data are commonly presented in various sections in the Electronic Patient Record (EPR) system and are not linked together, which can make it difficult for clinicians to consider all the data available. This multidisciplinary project aimed to incorporate patient quality of life questionnaires into the EPR system (EPIC) to allow for the reporting of post-surgical patient outcomes. By integrating these data into EPIC, the questionnaire could be embedded into the Extract-Transform-Load (ETL) data processes developed by the Digital Research Environment (DRE) at Great Ormond Street Hospital (GOSH), and therefore be incorporated into an automated dashboard alongside standard clinical data to alert clinicians to the health and treatment of patients. An R-Shiny dashboard was developed with design at the forefront by collaborating with human-computer design expertise to create an informative and interactive tool, called POTENTIAL, to track patient health and progress within the Specialist Neonatal and Adolescent Paediatric Surgery (SNAPS) department for patients with rare colorectal disease. The interactive dashboard focusses on providing clear and concise visualisations which describe the entire patient journey, highlighting key clinical events whilst under hospital supervision, and patient reported outcomes in the long-term monitoring of patient health.